O desafio contemporâneo para cidades na proteção das mulheres vítimas de violência doméstica: a Guarda Civil Metropolitana e aplicabilidade do Programa Guardiã Maria da Penha - Silva, Rubens Aparecido da (2023)
The purpose of this work is to demonstrate the Urban Security Public Policy applied by the Metropolitan Civil Guard in the protection of women victims of domestic violence, as well as the good intervention practices in the implementation and implantation of the Guardiã Maria da Penha Program, focusing on the technical actions of the specialized police work. Through a descriptive, exploratory and qualitative research, we propose to establish the quality of this public policy, applying a questionnaire to measure the satisfaction of the women assisted by the Guardiã Maria da Penha Program. There is a contemporary challenge for Smart and Sustainable Cities, to outline the skills of the Municipal Guards in these specific actions, which translates the specificities of action in a recalcitrant scenario of domestic violence, with a view to the social, economic and public health problem. The preservation of these women's lives is carried out through the interventions of the Guardiã Maria da Penha Program, which has become a successful paradigm of public policy and social action, with the objective of seeking real applicability in protecting the lives of women in vulnerable situations and risk.